Association Between ABO Blood Group and Venous Thromboembolism Risk in Patients With Peripherally Inserted Central Catheters: A Meta-analysis and Systematic Review - Zhang, Qiang; Peng, Hong; Hu, Lu; Ren, Ran; Peng, Xingqiao; Song, Jifang (Frontiers in Oncology, 2022)
Background Previous studies have evaluated the association between ABO blood group and venous thromboembolism (VTE) risk in patients with peripherally inserted central catheters (PICCs). However, it remains unclear whether ABO blood groups are associated with PICC-associated VTE risk. Therefore, we conducted a meta-analysis of related studies to elucidate the potential role of ABO blood group as a risk factor for PICC-associated VTE. Methods All detectable case–control and cohort studies comparing the role of ABO blood group as a risk factor for PICC-associated VTE were collected for this analysis by searching PubMed, Embase, CNKI, Web of Science and Wanfang. We conducted a meta-analysis of the eligible studies and computed the summary risk estimates with random or fixed effects models. Results A total of 4 studies involving 7804 patients were included. Meta-analysis of the studies showed that the risk of PICC-associated VTE was significantly higher in blood types A (OR=1.54, 95% CI=1.17 to 2.03), p=0.002), B (OR=2.35, 95% CI=1.71 to 3.23, p<0.0001), and AB (OR=2.55, 95% CI=1.68 to 3.88, p<0.0001) and lower in blood types O (OR=0.58, 95% CI=0.45 to 0.74, p<0.0001). Subgroup analysis based on ethnicity demonstrated that blood type O may be a genetic protective factor for PICC-associated VTE in Asians. Among Caucasians, individuals with blood types B and AB have a higher risk of PICC-associated VTE. Blood types A, B and AB are risk factors for PICC-associated VTE in Asians. Conclusions Blood type O is associated with a decreased risk of PICC-associated VTE, especially in Asian populations. Moreover, blood types A, B and AB are risk factors for PICC-associated VTE.